2001
DOI: 10.1021/jo015546y
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular [4 + 2] Cycloaddition Reaction of Six- and Seven-Membered Cyclic N-Allyl-C-arylethynyl Iminium Salts

Abstract: N-Allyl-2-(het)arylethynyl-3,4,5,6-tetrahydropyridinium triflates 1c,d,e and N-allyl-2-(het)aryl-4,5,6,7-tetrahydro-3H-azepinium triflates 1g,h undergo a thermal isomerization reaction leading to derivatives of [a,f]-annulated isoindolium salts 2 in good yields. Similarly, N-allyl-2-phenylethynyl-pyridinium triflate 4 is transformed into the condensed pyridinium salt 5. An intramolecular [4 + 2] cycloaddition reaction, in which the (het)arylethynyl moiety acts as the 4pi component, is considered as the key ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In preceding papers we have shown that the propyne iminium system, in which an iminium group is directly attached to a C≡C bond, resembles the acetylenic ketones under various aspects of reactivity, but features an even more electron poor acetylenic bond than the latter due to the presence of the cationic iminium function. As far as cycloaddition reactions are concerned, this could be confirmed for [4 + 2] cycloaddition reactions of propyne iminium salts with dienes (Diels-Alder reactions) [39][40][41][42][43] and for their reactivity toward muenchnones ( [3 + 2] cycloaddition with the incorporated azomethine ylide dipole and other reactions) [44]. In a preceding paper, we have described the remarkably high dipolarophilic reactivity of acetylenic iminium salts featuring a terminal C,C triple bond in [3 + 2] cycloaddition reactions with organoazides as 1,3-dipoles [45].…”
Section: Introductionmentioning
confidence: 86%
“…In preceding papers we have shown that the propyne iminium system, in which an iminium group is directly attached to a C≡C bond, resembles the acetylenic ketones under various aspects of reactivity, but features an even more electron poor acetylenic bond than the latter due to the presence of the cationic iminium function. As far as cycloaddition reactions are concerned, this could be confirmed for [4 + 2] cycloaddition reactions of propyne iminium salts with dienes (Diels-Alder reactions) [39][40][41][42][43] and for their reactivity toward muenchnones ( [3 + 2] cycloaddition with the incorporated azomethine ylide dipole and other reactions) [44]. In a preceding paper, we have described the remarkably high dipolarophilic reactivity of acetylenic iminium salts featuring a terminal C,C triple bond in [3 + 2] cycloaddition reactions with organoazides as 1,3-dipoles [45].…”
Section: Introductionmentioning
confidence: 86%
“…5-Chloromercuriuridine (9) undergoes a palladium-catalyzed C-allylation reaction with allyl triflate (eq 4). 5 Transmetalation of 5-chloromercuriuridine (9) and Palladium(II) Chloride generates the organopalladium(II) complex (10), which then reacts with allyl triflate to produce C-5 allyl-substituted uridine (11) for nitrone synthesis (eq 5). 6 The initial allylation produces the (E)-nitrone, which then isomerizes to the more stable (Z)-isomer.…”
Section: Original Commentarymentioning
confidence: 99%
“…The cycloisomerization of resulting pyridinium salt (36) afforded fused pyridinium triflate (37) in 73% yield (eq 10). 10 The synthesis of substituted oxindoles employing 5-exo-dig cyclization mainly depends on the nature of alkyne and conformation of amide in the precursor. Jones and Brunton performed a 5-exo-dig cyclization on precursor 39 as the key step in the synthesis of N-protected oxindole (40) in good yield.…”
Section: N-allylationmentioning
confidence: 99%
“…The methods for the preparation of alkyne iminium salts 1, which can formally be derived from aldehydes or ketones -or more exactly from vinylogous amides -have mainly been developed by Maas et al [2][3][4][5][6][7][8]. Alkinyl-alkoxymethyleniminium salts 2 have been prepared by the alkylation of propiolamides with triethyloxonium tetrafluoroborate [9][10][11][12][13][14] or methyl fluorosulfonate [15].…”
Section: Introductionmentioning
confidence: 99%